Numerical Investigation of Fracture Behavior for Glass Fiber Composite Concretes - Meryem Charef; Nabil Kazi Tani; Ahmed Soufiane Benosman; Hasan Dilbas (Journal of Building Materials and Structures)
Waste aggregate-based composite cementitious materials preserve natural resources and reduce environmental concerns throughout green concepts. In this view, recycled waste aggregate-based concrete and its innovative design require advanced computational modeling techniques. Accordingly, this comprehensive and computational research is conducted to investigate the fracture behavior of notched glass fiber reinforced concrete beam modeled with finite element method. The impacts of substitution ratios of the waste on strains and crack opening displacements of validated beam models are investigated and argued.